Pengaruh Model Problem Based Learning dengan Pendekatan Multirepresentasi terhadap Hasil Belajar Siswa pada Materi Usaha dan Energi - Elysabeth Joseph Mangngella; Yusuf Kendek (Universitas Tadulako, 2021)
This study aims to determine the effect of the problem-based learning model with a multi-representation approach on student learning outcomes on work and energy. The type of research used is an experimental design with